Blues for cannibals : the notes from underground - Bowden, Charles, 1945-2014 (University of Texas Press, 2018)
Cultivated from the fierce ideas seeded in Blood Orchid, Blues for Cannibals is an elegiac reflection on death, pain, and a wavering confidence in humanity's own abilities for self-preservation. After years of reporting on border violence, sex crimes, and the devastation of the land, Bowden struggles to make sense of the many ways in which we destroy ourselves and whether there is any way to survive. Here he confronts a murderer facing execution, sex offenders of the most heinous crimes, a suicidal artist, a prisoner obsessed with painting portraits of presidents, and other people and places that constitute our worst impulses and our worst truths. Painful, heartbreaking, and forewarning, Bowden at once tears us apart and yearns for us to find ourselves back together again.